2018
DOI: 10.18404/ijemst.408935
|View full text |Cite
|
Sign up to set email alerts
|

Using Tablets to Explore the Potential for Video-based Classroom Observations for Research and Professional Development

Abstract: This article may be used for research, teaching, and private study purposes. Any substantial or systematic reproduction, redistribution, reselling, loan, sub-licensing, systematic supply, or distribution in any form to anyone is expressly forbidden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Thus, it can be seen as a complement to direct contact with teaching practice, namely, to the observation of cooperating teachers' lessons, especially when the access to that practice may be undergoing several restrictions (Perry, et al 2022). In this way, the digital resources integrated into the multimedia cases, namely videos (Blazar et al, 2018), can be used as an alternative to meet the needs of an online teacher education, required by coping with the recent COVID-19 pandemic. These resources may mitigate the impacts that the abrupt and prolonged interruption of access to professional practice may cause to initial teacher education programmes (La Velle et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can be seen as a complement to direct contact with teaching practice, namely, to the observation of cooperating teachers' lessons, especially when the access to that practice may be undergoing several restrictions (Perry, et al 2022). In this way, the digital resources integrated into the multimedia cases, namely videos (Blazar et al, 2018), can be used as an alternative to meet the needs of an online teacher education, required by coping with the recent COVID-19 pandemic. These resources may mitigate the impacts that the abrupt and prolonged interruption of access to professional practice may cause to initial teacher education programmes (La Velle et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…According to Mcnulty and Lazarevic (2012), videos increase students' motivation to learn. For pre-service teachers, videos have helped them understand feedback and do self-reflection (Cavanagh, 2021) by watching their own teaching performances again to analyze their strengths and weaknesses (Blazar et al, 2018). Mcnulty and Lazarevic (2012) reveal that implementing videos in the classrooms enables students to make self-reflection and assessments in ELT.…”
Section: The Use Of Videos In English Language Teaching (Elt)mentioning
confidence: 99%
“…Technologically-assisted teaching and learning are already used in many classroom environments across the globe. Previous studies have indicated that teachers have tended to employ technologically-assisted tools in face-to-face classrooms (Blazar et al, 2018;Espino et al, 2020), such as listening, video watching, and Microsoft PowerPoint presentations. However, many teachers are not ready for full online teaching using distance-based learning tools and platforms (Moorhouse, 2020;Pike, 2015).…”
Section: Technology Should Be Employed In Educationmentioning
confidence: 99%